1995
DOI: 10.1107/s0108270194003914
|View full text |Cite
|
Sign up to set email alerts
|

A Macrobicyclic Thiophosphonamide Polyether Ligand

Abstract: Two crystal structures of a macrobicyclic oligoether compound, 31 -phenyl-8,11,14,17,20-pentoxa-1,27-diaza-31-phosphatetracyclo[25.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the course of our investigations to produce macrocyclic phosphorus ligands, we have been particularly interested by the cyclic derivatives obtained from the reaction of diamines with a diaminophosphine that can lead to macrocyclic phosphoramides [2][3][4][5][6]. From such compounds, nucleophilic attack at phosphorus could lead to new interesting structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of our investigations to produce macrocyclic phosphorus ligands, we have been particularly interested by the cyclic derivatives obtained from the reaction of diamines with a diaminophosphine that can lead to macrocyclic phosphoramides [2][3][4][5][6]. From such compounds, nucleophilic attack at phosphorus could lead to new interesting structures.…”
Section: Discussionmentioning
confidence: 99%
“…This article describes a new family of phosphorus ligands in which a phosphorylated binding site is introduced into a semirigid macrocyclic structure. We have recently shown that the synthesis of macrocyclic phosphonamides and the formation of metal ion complexes is possible through the combination of a crown ether unit and a phosphonamide-containing building block. …”
Section: Introductionmentioning
confidence: 99%
“…The standard strategy for the synthesis of macrocyclic phosphonamides is the preparation of an intermediate diamine followed by the cyclization of this diamine with a diaminophosphane, and finally oxidation of the parent phosphorus(III) macrocycle. , This general approach can be applied to a variety of diamines and diaminophosphanes, and syntheses of 17−27-membered-ring phosphorus crown compounds have been developed …”
Section: Introductionmentioning
confidence: 99%